Resonant power converter control for industrial magnetron - Abodhir, Nourdeen Abdulslam (2017)
High voltage DC power supplies have been used in a wide range of applications such as Radio Frequency (RF) tube drives, industrial, military, aerospace, medical, and domestic applications. Recently as a result of advances in power electronics and magnetic materials, development of compact high voltage DC power supplies has become an active area of research, and resonant power converters have been introduced as a promising solution, owing to their potential for high efficiency and high power density. Several resonant converter topologies have been investigated to be used as modulators for supplying RF tubes (i.e. Magnetrons, Klystrons, and Traveling Wave Tubes) for various applications. The main aim of this study is to develop a control methodology for maintaining soft switching of a series resonant series loaded (SRSL) power converter based modulator for driving an industrial magnetron with variable load conditions. This thesis considers the design of a high voltage, high frequency, compact power supply for applications where the load is variable and/or nonlinear. One particular application where this is the case is when driving an industrial magnetron with a variable output RF energy requirement. The magnetron appears to the resonant converter as a variable load which can negatively affect the efficiency of the power conversion unless control of the converter is carefully considered. A compact power supply based on the SRSL resonant converter with an extended combined phase and frequency control is proposed. A novel control method based on three dimensional (3D) lookup tables has been developed, in order to control the load resonant converter whilst maintaining soft switching under variable load conditions. A direct quadrature (DQ) based modelling approach is used to develop a suitable model of the converter for control design. Based on the characteristics of the magnetron, an emulator prototype is also proposed to represent the magnetron load behavior in a low voltage laboratory environment. A detailed design and implementation procedure is presented, including the hardware design and control of the resonant power converter and the magnetron emulator. Simulation and experimental results are provided to validate the approach and in order to demonstrate the feasibility of the proposed converter modelling approach and control strategy. A good correlation between simulation and experimental results is obtained.